In vivo phosphorylation patterns of key stressosome proteins define a second feedback loop that limits activation of Bacillus subtilis σ(B) - Eymann, Christine (2011)
The Bacillus subtilis stressosome is a 1.8 MDa complex that orchestrates activation of the σ(B) transcription factor by environmental stress. The complex comprises members of the RsbR co-antagonist family and the RsbS antagonist, which together form an icosahedral core that sequesters the RsbT serine-threonine kinase. Phosphorylation of this core by RsbT is associated with RsbT release, which activates downstream signaling. RsbRA, the prototype co-antagonist, is phosphorylated on T171 and T205 in vitro. In unstressed cells T171 is already phosphorylated; this is a prerequisite but not the trigger for activation, which correlates with stress-induced phosphorylation of RsbS on S59. By contrast, phosphorylation of RsbRA T205 has not been detected in vivo. Here we find (i) RsbRA is additionally phosphorylated on T205 following strong stresses; (ii) this modification requires RsbT; and (iii) the phosphorylation-deficient T205A substitution greatly increases post-stress activation of σ(B). We infer that T205 phosphorylation constitutes a second feedback mechanism to limit σ(B) activation, operating in addition to the RsbX feedback phosphatase. Loss of RsbX function increases the fraction of phosphorylated RsbS and doubly phosphorylated RsbRA in unstressed cells. We propose that RsbX both maintains the ready state of the stressosome prior to stress, and restores it post-stress.